2021
DOI: 10.1051/proc/202107002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of models for the simulation of landslide generated Tsunamis

Abstract: In this paper, we analyze the relevance of the use of the shallow water model and the Boussinesq model to simulate tsunamis generated by a landslide. In a first part, we determine if the two models are able to reproduce waves generated by a landslide. Each model has drawbacks but it seems that it is possible to use them together to improve the simulations. In a second part we try to recover the landslide displacement from the generated wave. This problem is formulated as a minimization problem and we limit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A switch between the two sets of equations allows to use the shallow water equations for a few instants during the water wave generation in the nearfield and the Boussinesq model for the far-field propagation. Indeed, Audusse et al (2021) showed that this combination of models improves the simulation of the generation process compared to using only the Boussinesq model.…”
Section: Depth-averaged Model: Avalanchementioning
confidence: 99%
“…A switch between the two sets of equations allows to use the shallow water equations for a few instants during the water wave generation in the nearfield and the Boussinesq model for the far-field propagation. Indeed, Audusse et al (2021) showed that this combination of models improves the simulation of the generation process compared to using only the Boussinesq model.…”
Section: Depth-averaged Model: Avalanchementioning
confidence: 99%
“…Trees in the forest have been used as seismic shields given their properties as natural metamaterials (Colquitt et al, 2017;Sewar et al, 2022). The numerical calculation of (2D) models, which ignores information about the propagation in the third direction, may lead to the loss of an essential calculation point (Audusse et al, 2021). Through a three dimension (3D) simulation model, which is a type of engineering, numerical analysis can be used to represent the visibility of an urban forest in a way that effectively protects against low-frequency EWs (Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A non-dispersion model is still a common approach for practical purposes and in coastal applications because it has a computational cost that is 3 to 4 times lower than that of dispersion. An example is seen in the recent work of Audusse et al (2019), where both models were compared in simulating tsunami waves generated by a landslide, and was discovered that the non-dispersion model performs better than that of dispersion in the generation zone but conversely in the propagation zone. Moreover, the non-dispersion model produces much less computational cost in terms of complexity compared to that of dispersion.…”
Section: Introductionmentioning
confidence: 99%